Síndromes reumáticos paraneoplásicos (2011)
ABSTRACT: A wide variety of rheumatic manifestations has been associated with malignancies. They may result from direct invasion of bone, joints or soft tissue by the tumor, and may also occur by distant effects of the tumor mediated by humoral factors (paraneoplastic syndromes). Among the paraneoplastic rheumatic syndromes, hyperthrophic ostearthropaty, carcinomatous polyarthritis, dermatomyositis and vasculitis are the most frequently diagnosed. Paraneoplastic syndromes may precede the tumor, by no longer than two years, appear simultaneously with it or follow its diagnosis. The clinical course usually is parallel to that of the tumor. Therefore, cure of the underlying malignancy often, although not invariably, results in regression of the paraneoplastic syndrome. In this article a review is presented on paraneoplastic rheumatic syndromes.